2020
DOI: 10.1111/mcn.12995
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural and empowerment pathways from land ownership to women's nutrition in India

Abstract: Land size is an important equity concern for the design of ‘nutrition‐sensitive’ agricultural interventions. We unpack some of the pathways between land and nutrition using a cross‐sectional baseline survey data set of 4,480 women from 148 clusters from the ‘Upscaling Participatory Action and Videos for Agriculture and Nutrition’ trial in Keonjhar district in Odisha, India. Variables used are household ln‐land size owned (exposure) and maternal dietary diversity score out of 10 food groups and body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…First, as mentioned by Harris-Fry et al [ 52 ], a temporal mismatch between agricultural production and diet assessment could affect the association between these two variables. Many studies were affected by a temporal mismatch with a reference period of 24-hour for dietary data and a reference period for agricultural production of one year [ 50 , 52 , 53 ] or one season [ 9 , 41 ]. In addition, previous studies have shown that women’s dietary diversity is sensitive to seasonality [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as mentioned by Harris-Fry et al [ 52 ], a temporal mismatch between agricultural production and diet assessment could affect the association between these two variables. Many studies were affected by a temporal mismatch with a reference period of 24-hour for dietary data and a reference period for agricultural production of one year [ 50 , 52 , 53 ] or one season [ 9 , 41 ]. In addition, previous studies have shown that women’s dietary diversity is sensitive to seasonality [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the assessment of the capacity of a production system to improve the diet is influenced by the choice of indicator of production diversity [ 34 ] but most studies are based on only one [ 9 , 50 52 ] or two [ 43 , 53 ] indicators. For example, Lourme-Ruiz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While farmers are less motivated to make plausible investments or participate in incomegenerating land contracts, the lack of entitlement and land ownership constraints agricultural development and can contribute to poor child health (Simbizi et al, 2014;Harris-Fry et al, 2020). Amidst global demographic growth, rapid urbanisation, environmental degradation and climate change, increased competition to acquire land raises the demand for land in Nigeria (Ghebru et al, 2014).…”
Section: Introductionmentioning
confidence: 99%